Oral Hygiene Awareness and Practices among a Sample of Primary School Children in Rural Bangladesh - Md. Al-Amin Bhuiyan; Humayra Binte Anwar; Rezwana Binte Anwar; Mir Nowazesh Ali; Priyanka Agrawal (MDPI AG, 2020)
Inadequate oral health knowledge and awareness is more likely to cause oral diseases among all age groups, including children. Reports about the oral health awareness and oral hygiene practices of children in Bangladesh are insufficient. Therefore, the objective of this study was to evaluate the oral health awareness and practices of junior school children in Mathbaria upazila of Pirojpur District, Bangladesh. The study covered 150 children aged 5 to 12 years of age from three primary schools. The study reveals that the students have limited awareness about oral health and poor knowledge of oral hygiene habits. Oral health awareness and hygiene practices amongst the school going children was found to be very poor and create a much-needed niche for implementing school-based oral health awareness and education projects/programs.